Novel monitoring of hepatitis B reactivation based on ultra‐high sensitive hepatitis B surface antigen assay. (29th January 2017) - Shinkai, Noboru; Kusumoto, Shigeru; Murakami, Shuko; Ogawa, Shintaro; Ri, Masaki; Matsui, Tekeshi; Tamori, Akihiro; Toyoda, Hidenori; Ishida, Takashi; Iida, Shinsuke; Tanaka, Yasuhito
Abstract: Background & Aims: Occult hepatitis B virus (HBV) infection should be evaluated before systemic chemotherapy to prevent HBV reactivation‐related hepatitis. We investigated HBV reactivation using high sensitivity HB surface antigen (HBsAg) chemiluminescent enzyme immunoassay (HBsAg‐HQ) and ultra‐high sensitive HBsAg assay employing a semi‐automated immune complex transfer chemiluminescence enzyme technique (ICT‐CLEIA). Methods: Of 120 HBV‐resolved patients with haematological malignancy receiving systemic chemotherapy from 2012 to 2015 in our hospital, 13 patients had HBV DNA reactivation (in 12/13 patients HBV DNA became quantifiable) according to HBV DNA monitoring. These patients were applied for Architect HBsAg‐QT (detection limit:50 mIU/mL), HBsAg‐HQ (5 mIU/mL) and ICT‐CLEIA (0.5 mIU/mL) using stored samples. Results: When HBV DNA was firstly quantifiable by regular HBV DNA monitoring, HBsAg‐QT was detected in 1/12 patients (8%), HBsAg‐HQ was detected in 4/12 patients (33%) and ICT‐CLEIA was detected in all 12 patients (100%), suggesting that the sensitivity of ICT‐CLEIA was comparable to that of HBV DNA quantification. Interestingly, two patients were HBsAg positive by ICT‐CLEIA before HBV DNA became detectable. Median difference of detectable point between HBV DNA and ICT‐CLEIA was zero (range from −28 to 56 days), while median delay by HBsAg‐QT or HBsAg‐HQ was 52.5 days after HBV DNA became detectable. Although anti‐HBs titres were high (131.9 mIU, 80.4 mIU) in two patients with escape mutations (Saa126V, Saa145R), HBsAg by ICT‐CLEIA and HBV DNA were detectable concurrently. Conclusions: ICT‐CLEIA is a novel assay for HBV monitoring to prevent hepatitis caused by HBV reactivation.